Participação social na avaliação de impacto ambiental: lições da experiência da Bahia - Francisca Neta Andrade Assunção; Maria Augusta Almeida Bursztyn; Teresa Lúcia Muricy de Abreu (Confins)
This paper analyzes the participation of the public society in the process of Environmental Impact Assessment (EIA) in the State of Bahia, Brazil. The aim is to understand up to what extent EIA is an effective contribution to the environmental licensing procedures, as an instrument of the Brazilian environmental policy. Social participation in Bahia can occur in three different moments. The first two are open to any citizen, but the last one is restricted to the representatives of the society in the State Council for the Environmental (Cepram), which decides about giving or not the licence. Research results demonstrate the existence of different degrees of participation of the society which vary according to aspects such as: the social and economic standards of the population affected by an intervention, the quality and the stock of natural resources, and the nature of the proprieties located in the area of intervention.